DDS技術を活用した体内再生誘導治療 - 澤本, 和延; 大塚, 隆信; 坪井, 義晃; 澤田, 雅人 (Drug Delivery System, 2017)
Endogenous stem cells are promising sources for low-cost and minimally invasive regenerative medicine. Recent studies suggest that drug delivery system technologies are useful to promote proliferation, differentiation and migration of various types of cells during regeneration processes. In this paper, we introduce recent progress in regenerative medicine using the drug delivery system.